The Effectiveness of Story Impression Strategy in Improving Ninth-Grade EFL Students’ Reading Comprehension: A Quasi-Experimental Study - Abidah, Siti; Suhartatik (Journey: Journal of English Language and Pedagogy, 2026)
This study was motivated by the low reading comprehension skills of ninth-grade junior high school students in English texts. Many students experience difficulty connecting new vocabulary to the story context, which impedes their comprehension. This quantitative research employed a quasi-experimental design to examine the effect of the Story Impression strategy on the English reading comprehension of ninth-grade students at SMPI Al-Muqorrobin. Two intact classes were involved: Class IX-A served as the experimental group (n = 19) and was taught using the Story Impression strategy, while Class IX-B functioned as the control group (n = 19) and received conventional instruction. Reading comprehension tests (pre-test and post-test) were used as the instrument, and the data were analyzed using Welch’s test in Microsoft Excel. The control group showed an improvement in the mean score from 38.68 on the pre-test to 62.86 on the post-test, while the experimental group demonstrated a greater increase from 48.75 on the pre-test to 90.00 otgn the post-test. Statistical testing confirmed that this increase was highly significant (p < 0.05), and the experimental group outperformed the control group on the final assessment. The findings demonstrate that the Story Impression strategy is highly effective in enhancing junior high school students’ reading comprehension.